Flexibility Management in Environmental Dynamic Supply Chain Management Study on Cracker Commodity in Surabaya City - Navandi, Dhony (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Supply chain management is a set of activities within a business process involving the production, delivery, storage, distribution and sale of the product in order to set up the existing requests will be fulfilled. The practice of supply chain management especially in the process of physical distribution of an item is very important for entrepreneurs. Flexibility management is capability company to quickly and effective adjust supplies, packaging, warehousing and transportation physical product to response to the need for customers. The purpose of this research which is to identify how the implementation of flexibility management in the supply chain management of cracker commodity in Surabaya city. The kind of this research is descriptive qualitative where use informant to find and collect data. In this research case is the factory, collectors and traders in traditional markets in Surabaya city. Conclusion of this research is flexibility management in supply chain management on cracker commodity in Surabaya city not properly applied and it is not too effective and efficient.